Update on treatment options for spinal brucellosis. (1st October 2013) - Ulu‐Kilic, A.; Karakas, A.; Erdem, H.; Turker, T.; Inal, A. S.; Ak, O.; Turan, H.; Kazak, E.; Inan, A.; Duygu, F.; Demiraslan, H.; Kader, C.; et al.
Abstract We evaluated the efficacy and tolerability of antibiotic regimens and optimal duration of therapy in complicated and uncomplicated forms of spinal brucellosis. This is a multicentre, retrospective and comparative study involving a total of 293 patients with spinal brucellosis from 19 health institutions. Comparison of complicated and uncomplicated spinal brucellosis was statistically analysed. Complicated spinal brucellosis was diagnosed in 78 (26.6%) of our patients. Clinical presentation was found to be significantly more acute, with fever and weight loss, in patients in the complicated group. They had significantly higher leukocyte and platelet counts, erythrocyte sedimentation rates and C‐reactive protein levels, and lower haemoglobulin levels. The involvement of the thoracic spine was significantly more frequent in complicated cases. Spondylodiscitis was complicated, with paravertebral abscess in 38 (13.0%), prevertebral abscess in 13 (4.4%), epidural abscess in 30 (10.2%), psoas abscess in 10 (3.4%) and radiculitis in 8 (2.7%) patients. The five major combination regimens were: doxycycline 200 mg/day, rifampicin 600 mg/day and streptomycin 1 g/day; doxycycline 200 mg/day, rifampicin 600 mg/day and gentamicin 5 mg/kg; doxycycline 200 mg/day and rifampicin 600 mg/day; doxycycline 200 mg/day and streptomycin 1 g/day; and doxycycline 200 mg/day, rifampicin 600 mg/day and ciprofloxacin 1 g/day. There were no significant therapeutic differences between these antibiotic groups; the results were similar regarding the complicated and uncomplicated groups. Patients were mostly treated with doxycycline and rifampicin with or without an aminoglycoside. In the former subgroup, complicated cases received antibiotics for a longer duration than uncomplicated cases. Early recognition of complicated cases is critical in preventing devastating complications. Antimicrobial treatment should be prolonged in complicated spinal brucellosis in particular.